Spatial Concept of Baluarti Keraton Kacirebonan - Ratna Puspita Dewi; Peri Puarag (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The Kacirebonan Palace in Cirebon City, known for its Javanese culture, houses a unique settlement surrounded by the Balutanti Fort. Baluarti Keraton Kacirebonan blends Chinese, Colonial, and Traditional-era buildings, preserving Javanese customs and procedures. However, challenges such as lack of authority, unclear preservation concepts, reliance on government subsidies, conflicts of interest, and low community participation hinder its preservation. This study uses Combined Strategies, combining Historical Research and Qualitative Research, to analyze objects from the past and examine their relationship with architectural design. Data sources include inscriptions, writings, and local experiences. Palaces often change over time, maintaining their architectural style by comparing new buildings with old ones. The roof shape, openings, and columns of new buildings often resemble those of the old building. The chessboard pattern, used for small towns with defense, agriculture, and trade functions, is also prevalent. Social factors and cultural influences significantly influence the spatial layout of a settlement. The Kacirebonan Palace complex, located southwest of Kasepuhan Palace and 500 meters south of Kanoman Palace, spans 46,500 square meters and features a Chinese-mixing style, Colonial, and Traditional era building. Baluarti settlement, part of the palace area, has a grid pattern with small, narrow roads, following the Palace's tradition. Baluarti, a Javanese settlement, is a residence for nobles, high-ranking priyayi, and courtiers of the Kacirebonan Palace. The settlement is characterized by a magersari system, where the king gives land for Abdidalem''s residence. The social status of the Baluarti community is derived from its family line, with most citizens having titles obtained from the king. Keraton Kacirebonan''s architecture blends Colonial, Chinese, and Javanese styles, while religious beliefs, social status, and the traditional magersari system influence the Baluarti settlement's layout.